Pulmonary storage with emphysema as a sign of Niemann-Pick type C2 disease (second complementation group). Report of a case - Elleder, M; Houstková, H; Zeman, J; Ledvinová, J; Poupetová, H (Virchows Archiv, 2001)
A case is described of Niemann-Pick type C2 disease presenting an infantile pneumopathic phenotype known to occur in this recently established, second, minor complementation group of Niemann-Pick type C (NPC) disease. However, the pulmonary involvement was unique, being dominated, in addition to the usual storage macrophage infiltration of the alveolar and septal compartments, by irregular emphysema attributed to storage cell migration into the bronchiolar lumen. The latter modified considerably the X-ray findings and hindered the initial clinical diagnosis. Otherwise, the storage phenotype, including the range of stored lipids, storage distribution, and cell and organ pathology, was found to be identical to that in the whole Niemann-Pick type C disease group dominated by NPC1. The biochemical findings (cholesterol esterification level) corresponded to the classical biochemical phenotype. Emphysema should thus be considered as a variant of the pulmonary NPC2 storage process, governed most probably by an epigenetic mechanism responsible for storage macrophage migration into the bronchiolar compartment.
Keywords: intersticiální plicní nemoci; Niemann-Pick Diseases; respirační insuficience; glykosfingolipidy; plíce; Niemannova-Pickova nemoc; rentgendiagnostika hrudníku; Emphysema; emfyzém; fatální výsledek; Glycosphingolipids; neurony; Fatal Outcome; Lung; novorozenec; Radiography, Thoracic; lidé; ženské pohlaví; Humans; Neurons; Infant, Newborn; makrofágy; Lung Diseases, Interstitial; Respiratory Insufficiency; Female; Macrophages